Posttransplant Complications and Genetic Loci Involved in Telomere Maintenance in Heart Transplant Patients - Dlouha, Dana; Vymetalova, Jevgenija; Novakova, Sarka; Huckova, Pavlina; Lanska, Vera; Hubacek, Jaroslav Alois (Genes, 2022)
Reaching critically short telomeres induces cellular senescence and ultimately cell death. Cellular senescence contributes to the loss of tissue function. We aimed to determine the association between variants within genes involved in telomere length maintenance, posttransplant events, and aortic telomere length in heart transplant patients. DNA was isolated from paired aortic samples of 383 heart recipients (age 50.7 ± 11.9 years) and corresponding donors (age 38.7 ± 12.0 years). Variants within the TERC (rs12696304), TERF2IP (rs3784929 and rs8053257), and OBCF1 (rs4387287) genes were genotyped, and telomere length was measured using qPCR. We identified similar frequencies of genotypes in heart donors and recipients. Antibody-mediated rejection (AMR) was more common (p < 0.05) in carriers of at least one G allele within the TERF2IP locus (rs3784929). Chronic graft dysfunction (CGD) was associated with the TERC (rs12696304) GG donor genotype (p = 0.05). The genetic risk score did not determine posttransplant complication risk prediction. No associations between the analyzed polymorphisms and telomere length were detected in either donor or recipient DNA. In conclusion, possible associations between donor TERF2IP (rs3784929) and AMR and between TERC (rs12696304) and CGD were found. SNPs within the examined genes were not associated with telomere length in transplanted patients.
Keywords: Humans; transplantace srdce; lidé středního věku; Leukocytes; rejection; telomere; telomery; genetic risk score; genetické lokusy; dospělí; lidé; Heart Transplantation; DNA; Adult; Telomere; Middle Aged; heart transplantation; Genetic Loci; leukocyty; SNP